The efficiency of tear substitute therapy at dysfunction tear basic secretion - G. S. Polunin; A. O. Zabegaylo; I. A. Makarov; T. N. Safonova; E. G. Polunina; A. V. Zhemchugova; A. Alieva (Oftalʹmologiâ)
Purpose: to evaluate the efficiency and tolerance of drops replacing tear with hyaluronic acid 0.15% (Hylabak, thea, France) for the treatment of tear film diseases, in particular blepharoconjunctival form of dry eye syndrome.Methods: 32 patients (range 38 to 72 years) with blepharoconjunctival form of dry eye syndrome were treated lubricant Hylabak 2-4 times a day during 7-30 days.Results: After treatment was detected the elimination of complaints in 30 of 32 people, increasing the stability of the tear film (increasing values of the samples Norn test from 7.3 ±0.5 to 10.1±0.6 seconds), as well as normalization of Schirmer test (from 8.8±0.4 to 15.2±0.5 mm).Conclusion: the study was showed high efficacy of lubricant Hylabak and subjective tolerability at blepharoconjunctival form of dry eye syndrome.